2016
DOI: 10.1111/os.12280
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of Japanese Orthopaedic Association Scoring Systems with Gait Parameters in Patients with Degenerative Spinal Diseases

Abstract: There is a significant correlation between gait parameters and functional disability as measured by the JOA lumbar scoring system, which indicates that the JOA lumbar scoring system can reflect gait impairment. The JOA cervical scoring system, however, may need to be improved for efficiently evaluating the walking ability of CSM patients in the assessment of motor function of the lower extremity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
(32 reference statements)
0
14
0
1
Order By: Relevance
“…In a systematic review of the literature, accelerometer and physical activity analyses using wearable devices ranked among the top five most frequently applied methods for objective outcome measurement in spine care 4 . To date, the activity levels of about 340 patients with lumbar degenerative diseases of the spine have been reported in nine research articles, which included patients with low back pain (LBP), lumbar spinal stenosis (LSS) and lumbar disc herniation (LDH) [8][9][10][11][12][13][14][15][16] .…”
mentioning
confidence: 99%
“…In a systematic review of the literature, accelerometer and physical activity analyses using wearable devices ranked among the top five most frequently applied methods for objective outcome measurement in spine care 4 . To date, the activity levels of about 340 patients with lumbar degenerative diseases of the spine have been reported in nine research articles, which included patients with low back pain (LBP), lumbar spinal stenosis (LSS) and lumbar disc herniation (LDH) [8][9][10][11][12][13][14][15][16] .…”
mentioning
confidence: 99%
“…In contrast to the large amount of literature surrounding gait analysis in other neurological conditions [28], such as stroke [29], Parkinson's disease, and other neurological conditions [26], little is known about specific spatiotemporal gait parameters in DCM [9,28]. In a recent publication, Zheng et al [30] evaluated the correlation between the JOA score and specific gait parameters in patients with DCM and lumbar disc herniation (LDH). They found only a weak correlation between the JOA score and step duration, cycle duration, double-support time, gait speed, cadence, and stride length and no correlation with single-support time.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our study shows a significant and moderately strong correlation between the mJOA score and both velocity and step length, as well as a relatively strong correlation between the mJOA score and the eGVI. Zheng et al [30] state that the JOA scoring system might not adequately reflect gait impairment and that gait analysis might be more reliable in detecting walking impairment. Since they found a better correlation between the JOA lumbar score and gait parameters, they suggested that the difference might be due to the use of fewer questions regarding walking in the JOA cervical score.…”
Section: Discussionmentioning
confidence: 99%
“…Plain film radiography and dynamic lateral radiography of the cervical vertebra, CT scan, and MRI examination were performed. JOA scores, 40‐point scores, visual analogue scales (VAS), neck disability index (NDI), and Nurick scores were recorded.…”
Section: Methodsmentioning
confidence: 99%